Evaluation of Functional Electrical Stimulation to Assist Cycling in Four Adolescents with Spastic Cerebral Palsy - Ann Tokay Harrington; Calum G. A. McRae; Samuel C. K. Lee (International Journal of Pediatrics)
Introduction. Adolescents with cerebral palsy (CP) often have difficulty participating in exercise at intensities necessary to improve cardiovascular fitness. Functional electrical stimulation- (FES-) assisted cycling is proposed as a form of exercise for adolescents with CP. The aims of this paper were to adapt methods and assess the feasibility of applying FES cycling technology in adolescents with CP, determine methods of performing cycling tests in adolescents with CP, and evaluate the immediate effects of FES assistance on cycling performance. Materials/Methods. Four participants (12–14 years old; GMFCS levels III-IV) participated in a case-based pilot study of FES-assisted cycling in which bilateral quadriceps muscles were activated using surface electrodes. Cycling cadence, power output, and heart rate were collected. Results. FES-assisted cycling was well tolerated (n=4) and cases are presented demonstrating increased cadence (2–43 rpm), power output (19–70%), and heart rates (4-5%) and decreased variability (8–13%) in cycling performance when FES was applied, compared to volitional cycling without FES assistance. Some participants (n=2) required the use of an auxiliary hub motor for assistance. Conclusions. FES-assisted cycling is feasible for individuals with CP and may lead to immediate improvements in cycling performance. Future work will examine the potential for long-term fitness gains using this intervention.